PENERAPAN GEOSPASIAL BERBASIS WEB UNTUK PEMETAAN ACARA DAN PENGALIHAN JALUR LALU LINTAS FESTIVAL TAHUNAN DI KECAMATAN BANYUWANGI - Alfi Fahira Salsabila; Zaehol Fatah; Anwar Anas (CV. Denasya Smart Publisher, 2025)
This research designs and develops a web-based Geographic Information System (GIS) for event mapping and traffic diversion for annual festivals in Banyuwangi Regency. The main objective is to simplify access to information related to festivals, routes, and traffic diversions for tourists, the general public, and Transportation Agency staff. Thus, this system is designed to assist in preventing traffic congestion and improving safety during festivals. The research methodology follows the Waterfall model, which consists of five steps: needs analysis, system design, development, testing and evaluation, and system deployment along with maintenance. Data collection was conducted through desk research and field research using observation, interviews, and document collection. The system interface consists of a main menu and four features: homepage, routes, paths, and festival information. This GIS integrates spatial data (maps) and non-spatial data (information about the festival) to provide unique visualizations that can be accessed online. This system is expected to assist the Transportation Agency in traffic management, provide safety for road users, and enable a more systematic and efficient management of annual festivals.